Aggression, Victimization and Sexual Harassment among Young Adolescents in Turkey - Ulubas, Isik Z.; Kaj Björkqvist; Karin Österman (European Journal of Social Science Education and Research, 2021)
The study investigates sex differences and regional differences in both victimization and perpetration of aggression and sexual harassment in Turkey. A questionnaire was completed by 482 young adolescents (9?15 years of age) from four regions in Turkey. Six different forms of aggression (physical, verbal, indirect, cyber, verbal sexual harassment, and physical sexual harassment) were examined in relation to sex and region. Sex differences were found both regarding victimization from and perpetration of aggression. Boys were found to perpetrate and become victimized more from sexual harassment than girls. Regional differences were found, with young adolescents from the Southeast region scoring higher than others on some forms of victimization and perpetration of aggression. The results are compared with previous findings and possible causes for the aggression are discussed.
Keywords: Aggression, Victimization, Sexual Harassment, Adolescents